Design, Synthesis, Structural Insights, Tyrosinase Inhibition, and Sun Protection Factor of New Thiosemicarbazone Derivatives - Sebastiano Masuri; Benedetta Era; Francesca Pintus; Sonia Floris; Francesca Meloni; Francesca Pettinau; Enrico Podda; Maria Grazia Cabiddu; Antonella Fais; Tiziana Pivetta (Molecules)
Tyrosinase, a key protein in the biosynthesis of melanin pigments, is crucial in determining skin pigmentation. Inhibiting tyrosinase activity is a promising approach for treating conditions related to excessive pigmentation. For the synthesis of more potent tyrosinase inhibitors, we combined two approaches, para-substitution and lipophilicity, to enhance the inhibitory properties of (E)-2-(4-hydroxybenzylidene)hydrazine-1-carbotiamide, whose enzyme inhibitory properties have been previously demonstrated. The newly synthesized compounds showed potent inhibition activity against tyrosinase in the micromolar concentration range. The synthesised compounds were up to 41 times more effective than kojic acid. In addition to this biological activity, all molecules were evaluated for their sun protection factor to determine their photoprotective effects. All the compounds showed higher efficacy than reference compounds, used as sunscreens in photoprotective preparations. All compounds were noncytotoxic at the concentration required to inhibit tyrosinase activity. With the aim of defining the potential binding modes and the kind of interactions between the studied molecules and the catalytic site of mushroom tyrosinase, molecular docking simulations were also performed.